Bromatological quality and productivity of hydroponic maize forage cultivated in different substrates (Research, Society and Development, 2020)
The objective of this work was to evaluate the productivity and the chemical quality of hydroponic corn forage grown on different substrates. The experiment was conducted at the Federal Institute of Science and Technology of Roraima – Campus Novo Paraíso, in the municipality of Caracaraí, Roraima, Brazil. The experiment was carried out in a randomized block design, with five sowing rates (treatments) and four replications. Hybrid corn seeds 2022 were used, sown on a double-sided canvas. When germination started, fertigation with nutrient solution was carried out. The evaluation occurred on the 10th day after sowing and included determination of plant height (cm) and roughage productivity (kg m² and t ha-¹) and bromatological analyses (% N, PB, FDA, NDF and NDT). For bromatological analyses, corn plants were collected, dried in an oven at 65 ºC and then crushed. The productivity of natural forage (k m² and t ha-¹), plant height and the neutral fiber content (NDF) of hydroponic corn were higher at the sowing rate of 2.5 kg m². These variables were influenced by the sowing rate and type of substrate, but resulted in a lower crude protein content. The results show that sugarcane bagasse was a suitable substrate for hydroponic corn, which is justified by the fact that it presents fewer moisture losses, avoiding the loss of nutrients in the nutrient solution. At a sowing rate of 1.0 kg m², the forage produced had a higher content of nitrogen, crude protein and total digestible nutrients, which are important for animal nutrition.